Risk of thrombotic complications in influenza versus COVID‐19 hospitalized patients. Issue 3 (8th April 2021) - Stals, Milou A. M.; Grootenboers, Marco J. J. H.; van Guldener, Coen; Kaptein, Fleur H. J.; Braken, Sander J. E.; Chen, Qingui; Chu, Gordon; van Driel, Erik M.; Iglesias del Sol, Antonio; de Jonge, Evert; Kant, K. Merijn; Pals, Fleur; et al.
Abstract: Background: Whereas accumulating studies on patients with coronavirus disease 2019 (COVID‐19) report high incidences of thrombotic complications, large studies on clinically relevant thrombosis in patients with other respiratory tract infections are lacking. How this high risk in COVID‐19 patients compares to those observed in hospitalized patients with other viral pneumonias such as influenza is unknown. Objectives: To assess the incidence of venous and arterial thrombotic complications in hospitalized patients with influenza as opposed to that observed in hospitalized patients with COVID‐19. Methods: This was a retrospective cohort study; we used data from Statistics Netherlands (study period: 2018) on thrombotic complications in hospitalized patients with influenza. In parallel, we assessed the cumulative incidence of thrombotic complications—adjusted for competing risk of death—in patients with COVID‐19 in three Dutch hospitals (February 24 to April 26, 2020). Results: Of the 13 217 hospitalized patients with influenza, 437 (3.3%) were diagnosed with thrombotic complications, versus 66 (11%) of the 579 hospitalized patients with COVID‐19. The 30‐day cumulative incidence of any thrombotic complication in influenza was 11% (95% confidence interval [CI], 9.4–12) versus 25% (95% CI, 18–32) in COVID‐19. For venous thrombotic (VTC) complications and arterial thrombotic complications alone, these numbers were, respectively, 3.6% (95% CI, 2.7–4.6) and 7.5% (95% CI, 6.3–8.8) in influenza versus 23% (95% CI, 16–29) and 4.4% (95% CI, 1.9–8.8) in COVID‐19. Conclusions: The incidence of thrombotic complications in hospitalized patients with influenza was lower than in hospitalized patients with COVID‐19. This difference was mainly driven by a high risk of VTC complications in the patients with COVID‐19 admitted to the Intensive Care Unit. Remarkably, patients with influenza were more often diagnosed with arterial thrombotic complications. Abstract :